Effectiveness of an andiroba oil bioproduct in maintaining egg quality at room temperature - Rufino, João Paulo Ferreira; Araújo, Bárbara Souza de; Moda, Rebeca Fontenele; Guimarães, Cristiane Cunha; Santos, Adriene Núzia de Almeida; Chaves, Francisco Alberto de Lima; Silva Junior, Joel Lima da; Mendonça, Marco Antonio de Freitas; Mendes, Joana Maia; Lima, Emersom Silva; Machado, Noedson de Jesus Beltrão; Pereira, Anderson Mathias; et al. (Food Science and Technology, 2026)
The aim of this study was to evaluate the effectiveness of a bioproduct based on andiroba oil (AO; Carapa guianensis) in preserving the physical, bacteriological, and chemical qualities of chicken eggs stored at room temperature for 7 days. Eggs were treated with different concentrations of AO (1–15%), two application methods (spray or immersion), and two exposure times (15 and 30 s). The bioproduct effectively reduced microbial load, particularly Escherichia coli, Staphylococcus aureus, and Salmonella spp., and improved the conservation of egg weight, albumen and yolk height, shell thickness, and Haugh unit (HU). Higher oil concentrations, especially at 15% with immersion for 30 s, provided the best results by forming a protective film that minimized gas and moisture exchange. Additionally, the coating reduced lipid oxidation and maintained yolk lipid content, confirming the protective and antioxidant action of the bioproduct. Although higher oil concentrations slightly affected sensory acceptance, the product proved to be a promising natural alternative to refrigeration for short-term egg storage in tropical conditions.